Annex and rigid diaphragm effects on the failure analysis and earthquake damages of historic churches. (January 2016) - Dal Cin, A.; Russo, S.
Abstract: Historical churches, in the most of cases, are characterised by the presence of annexes and rigid diaphragm that influence their seismic response. Therefore, this research aims to investigate the disadvantages and the benefits which emerge during the horizontal dynamic actions between these structures. This study presents some analyses carried out on the Gesù Church in Mirandola, which was damaged by the 2012 Northern Italy earthquake. The first fundamental steps have been the geometrical, material and in particular the seismic damage survey. An undamaged finite element model of the actual configuration of the Gesù church with a perfectly connected annex was created and was also considered the same model as an isolated structure. Through these FE models preliminary modal dynamic analyses were conducted in the linear elastic field. Subsequently non-linear static analyses were carried out to investigate the ultimate capacity of the building. The churches are characterised by large halls without internal thorn walls, slender walls, pushing elements and lack of intermediate horizontal connection. All these factors lead each macroelement to have an independent dynamics, showing the absence of box-like behaviour. Since the roof trusses are one of the few structural elements that can determine a better global behaviour, it has been decided to perform the same numerical analyses even in the FE models without the roof, then considering the extreme case of a not effective simply supported roof. Highlights: The analysis of the seismic interaction between church and annex Global greater seismic capacity in the church/annex configurations compared with the isolated structure The rigid diaphragm, as a well structural covering, present a significant increase in seismic capacity. Redistribution of the seismic load among the macroelements, with a significant increase in those of the unconstrained side.